2019
DOI: 10.5472/marumj.570908
|View full text |Cite
|
Sign up to set email alerts
|

Energy drink consumption among pre-clinical medical students attending a public medical school in Istanbul, Turkey

Abstract: Objective: It has been reported that energy drink usage is increasing worldwide despite reports of severe adverse health effects. This study aimed to explore pre-clinical medical students' attitudes and perceptions in relation to energy drinks.Materials and Methods: This was a questionnaire-based descriptive study of pre-clinical medical students attending a public medical school in Istanbul, Turkey. Questions covered the students' sociodemographic characteristics, personal habits (e.g., smoking and alcohol co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The prevalence of ED consumption was 30.6%, and the prevalence of ED mixed alcohol consumption was 9.5% in this study. Kulak et al 21 reported that 68% of university students consumed ED at least once in their lives, and Reid et al 2 reported the prevalence of ED consumption among university students as 86%, and these rates are quite high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of ED consumption was 30.6%, and the prevalence of ED mixed alcohol consumption was 9.5% in this study. Kulak et al 21 reported that 68% of university students consumed ED at least once in their lives, and Reid et al 2 reported the prevalence of ED consumption among university students as 86%, and these rates are quite high.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the students mostly reported that they consumed ED for having fun and being able to take more alcohol. The reasons for consuming ED among young people were getting prepared for physical activity, 21 decreasing tiredness, 3,21 enjoying its taste, 15 trying to stay awake and study, 22 and being able to drink more alcohol. 9 In this study, 17.3% of the students consumed ED mixed alcohol in the last year; 11.6% of the students consumed energy mixed alcohol drinks in the last 30 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation